Choosing blocks for spatial cross-validation: lessons from a marine remote sensing case study - Stock, Andy (Frontiers in Remote Sensing, 2025)
Supervised learning allows broad-scale mapping of variables measured at discrete points in space and time, e.g., by combining satellite and in situ data. However, it can fail to make accurate predictions in new locations without training data. Training and testing data must be sufficiently separated to detect such failures and select models that make good predictions across the study region. Spatial block cross-validation, which splits the data into spatial blocks left out for testing one after the other, is a key tool for this purpose. However, it requires choices such as the size and shape of spatial blocks. Here, we ask, how do such choices affect estimates of prediction accuracy? We tested spatial cross-validation strategies differing in block size, shape, number of folds, and assignment of blocks to folds with 1,426 synthetic data sets mimicking a marine remote sensing application (satellite mapping of chlorophyll a in the Baltic Sea). With synthetic data, prediction errors were known across the study region, allowing comparisons of how well spatial cross-validation with different blocks estimated them. The most important methodological choice was the block size. The block shape, number of folds, and assignment to folds had minor effects on the estimated errors. Overall, the best blocking strategy was the one that best reflected the data and application: leaving out whole subbasins of the study region for testing. Correlograms of the predictors helped choose a good block size. While all approaches with sufficiently large blocks worked well, none gave unbiased error estimates in all tests, and large blocks sometimes led to an overestimation of errors. Furthermore, even the best choice of blocks reduced but did not eliminate a bias to select too complex models. These results 1) yield practical lessons for testing spatial predictive models in remote sensing and other applications, 2) highlight the limitations of model testing by splitting a single data set, even when following elaborate and theoretically sound splitting strategies; and 3) help explain contradictions between past studies evaluating cross-validation methods and model transferability in remote sensing and other spatial applications of supervised learning.